Inhibition of IFN-γ-dependent antiviral airway epithelial defense by cigarette smoke - El-Mahdy Sherif; Manzel Lori J; Modestou Modestos A; Look Dwight C (Respiratory Research, 2010)
Abstract Background Although individuals exposed to cigarette smoke are more susceptible to respiratory infection, the effects of cigarette smoke on lung defense are incompletely understood. Because airway epithelial cell responses to type II interferon (IFN) are critical in regulation of defense against many respiratory viral infections, we hypothesized that cigarette smoke has inhibitory effects on IFN-γ-dependent antiviral mechanisms in epithelial cells in the airway. Methods Primary human tracheobronchial epithelial cells were first treated with cigarette smoke extract (CSE) followed by exposure to both CSE and IFN-γ. Epithelial cell cytotoxicity and IFN-γ-induced signaling, gene expression, and antiviral effects against respiratory syncytial virus (RSV) were tested without and with CSE exposure. Results CSE inhibited IFN-γ-dependent gene expression in airway epithelial cells, and these effects were not due to cell loss or cytotoxicity. CSE markedly inhibited IFN-γ-induced Stat1 phosphorylation, indicating that CSE altered type II interferon signal transduction and providing a mechanism for CSE effects. A period of CSE exposure combined with an interval of epithelial cell exposure to both CSE and IFN-γ was required to inhibit IFN-γ-induced cell signaling. CSE also decreased the inhibitory effect of IFN-γ on RSV mRNA and protein expression, confirming effects on viral infection. CSE effects on IFN-γ-induced Stat1 activation, antiviral protein expression, and inhibition of RSV infection were decreased by glutathione augmentation of epithelial cells using N-acetylcysteine or glutathione monoethyl ester, providing one strategy to alter cigarette smoke effects. Conclusions The results indicate that CSE inhibits the antiviral effects of IFN-γ, thereby presenting one explanation for increased susceptibility to respiratory viral infection in individuals exposed to cigarette smoke.